ChemInform Abstract: (+)‐ and (‐)‐Ganodilactone, a Pair of Meroterpenoid Dimers with Pancreatic Lipase Inhibitory Activities from the Macromycete Ganoderma leucocontextum. Issue 48 (10th November 2016) - Chen, He‐Ping; Zhao, Zhen‐Zhu; Zhang, Yu; Bai, Xue; Zhang, Ling; Liu, Ji‐Kai
Abstract: (+)‐ and (‐)‐Ganodilactone (I) from the fruiting bodies of Ganoderma leucocontextum are a pair of novel meroterpenoid dimers possessing a unique 5′H‐spiro[chroman‐4, 2′‐furan]‐2, 5′‐dione ring system.